Characteristics and origins of viscoelastic turbulence in a 3-stream contraction-expansion micro-channel - Tai, Jiayan (2016)
At low Reynolds number (Re < 1), the flow of viscous liquids e.g. water, is laminar. An aqueous solution e.g. water becomes viscoelastic when a small amount of polymer additives (< 1 wt%) is added to it; its flow behavior can become drastically different and turbulent i.e. viscoelastic turbulence. This phenomenon has gained increasing attention because it violates the conventional school of thought i.e. high- Re criteria, for creating chaos and disorder in a fluid dynamics system. As the polymer molecules are invisible, the indirect deduction of molecular behavior via motion analyses of tracer additives has been adopted as the main investigative approach in viscoelastic turbulent flows. Based on this approach, reported works attribute viscoelastic turbulence to the release of elastic energy by the polymer molecules, which had been extended due to strong velocity gradients in the flow field. The release of energy occurs over a range of time scales which is dependent on the characteristic time scales of the molecules and bulk viscoelastic liquid. Although the reported characteristic time scales vary significantly, their effects on the structure of the viscoelastic turbulent flow field have not been investigated.